Scaffolding for Repair: Understanding Molecular Functions of the SMC5/6 Complex - Diaz, Mariana; Pecinka, Ales (Genes, 2018)
Chromosome organization, dynamics and stability are required for successful passage through cellular generations and transmission of genetic information to offspring. The key components involved are Structural maintenance of chromosomes (SMC) complexes. Cohesin complex ensures proper chromatid alignment, condensin complex chromosome condensation and the SMC5/6 complex is specialized in the maintenance of genome stability. Here we summarize recent knowledge on the composition and molecular functions of SMC5/6 complex. SMC5/6 complex was originally identified based on the sensitivity of its mutants to genotoxic stress but there is increasing number of studies demonstrating its roles in the control of DNA replication, sister chromatid resolution and genomic location-dependent promotion or suppression of homologous recombination. Some of these functions appear to be due to a very dynamic interaction with cohesin or other repair complexes. Studies in Arabidopsis indicate that, besides its canonical function in repair of damaged DNA, the SMC5/6 complex plays important roles in regulating plant development, abiotic stress responses, suppression of autoimmune responses and sexual reproduction.
Keywords: SMC5/6; chromosomes; genome stability; DNA damage repair; Structural maintenance of chromosomes; chromatin